2008
DOI: 10.3168/jds.2008-1405
|View full text |Cite
|
Sign up to set email alerts
|

Milk Production Change Following Clinical Mastitis and Reproductive Performance Compared Among J5 Vaccinated and Control Dairy Cattle

Abstract: Naturally occurring cases of bovine clinical mastitis (CM) were studied among J5 vaccinates and controls on 3 commercial dairy farms. Milk production change and reproductive performance following CM were compared between the 2 groups. Among 306 controls and 251 vaccinates, there were 221 new cases of CM affecting 120 cows; 437 lactations never had a case of CM. Environmental pathogens made up 90% (159/176) of etiologic agents isolated. Change in daily milk production following CM was associated with J5 vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 27 publications
2
28
0
4
Order By: Relevance
“…Dobson et al (2008) reported that it took more than an extra 40 and 18 days, respectively, to get a lame or mastitic cow in-calf compared with healthy herd mates. Wilson et al (2008) reported that cows were significantly less likely to become pregnant if infected by Escherichia coli (42% pregnant) or Streptococcus spp. (38% pregnant) compared with cows with no mastitis (78% pregnant).…”
Section: Genetic Correlationsmentioning
confidence: 99%
“…Dobson et al (2008) reported that it took more than an extra 40 and 18 days, respectively, to get a lame or mastitic cow in-calf compared with healthy herd mates. Wilson et al (2008) reported that cows were significantly less likely to become pregnant if infected by Escherichia coli (42% pregnant) or Streptococcus spp. (38% pregnant) compared with cows with no mastitis (78% pregnant).…”
Section: Genetic Correlationsmentioning
confidence: 99%
“…Neste perí-odo, a média de produção de vacas não vacinadas (J5Vcont) foi de 21,26 kg de leite/vaca/dia, enquanto as vacinadas (J5V) apresentaram média de produção 22,79 kg de leite/ vaca/dia, ou seja, o grupo não vacinado produziu 1,53 kg de leite/vaca/dia a menos comparado ao grupo vacinado. Um estudo realizado por Wilson et al (2008) relatou que a vacinação com E.coli J5 esteve associada à menor redução na produção de leite, após casos clínicos de mastite, em vacas vacinadas comparada às controles. Vacas vacinadas apresentaram uma produção diária de leite de 7 a 16 kg maior que vacas não vacinadas cerca de três semanas após a manifestação do caso clínico de mastite, com início nos primeiros 50 dias de lactação, e aproximadamente 2 kg de leite a mais durante toda a lactação.…”
Section: Resultsunclassified
“…Os resultados aqui apresentados, em conjunto com os achados de Wilson et al (2007Wilson et al ( , 2008, indicam que a imunização com E. coli J5 está relacionada ao retorno mais rá-pido da produção de leite após o caso clínico, uma vez que ocorre redução na intensidade dos sinais clínicos, permitindo o restabelecimento das funções de produção da glân-dula mamária, com menores efeitos deletérios na produção de leite durante a lactação.…”
Section: Resultsunclassified
“…A exposição deste, estimula a produção de imunoglobulinas que possuem reação cruzada contra os antígenos de núcleo de outras bactérias, resultando em imunidade associada à proteção contra uma variedade de gêneros e cepas de bactérias (WILSON et al, 2008). A utilização de E. coli J5 aumenta os títulos séricos e do leite de anticorpos específi cos contra o LPS de E. coli J5, intensifi cando sua opsonização, bem como reduzindo a incidência e intensidade dos casos clínicos de mastite por coliformes (GONZÁLEZ et al, 1989;BAUMGARTNER et al, 1991;HOGAN et al, 1995).…”
Section: A Bactéria Escherichia Coliunclassified